Syntheses and N-methyl-D-aspartate Receptor Antagonist Pharmacology of Fluorinated Arylcycloheptylamines - Sun, Shengguo; Wallach, Jason; Adejare, Adeboye (Medicinal Chemistry, 2014)
Selective uncompetitive antagonists of the phencyclidine (PCP) binding site of the N-methyl-D-aspartate receptor (NMDAR) are known to have therapeutic potential as anticonvulsants and neuroprotective agents. Several fluorinated molecules with each containing a cycloheptane ring were designed to probe the PCP pharmacophore and test the influence of fluorine substitution on NMDAR binding and in vivo efficacy. Syntheses and analyses of six novel compounds, 1-(4- fluorophenyl)cycloheptanamine (3), 1-(1-(4-fluorophenyl)cycloheptyl)piperidine (4), 1-(1-(4-fluorophenyl)cycloheptyl) pyrrolidine (5), 1-(3-fluorophenyl)cycloheptanamine (6), 1-(1-(3-fluorophenyl)cycloheptyl)piperidine (7), 1-(1-(3-fluorophenyl) cycloheptyl)pyrrolidine (8) and several related reference arylcyloalkylamines are described. Receptor binding was performed at the PCP site of NMDAR for each compound using [3H]-(+)-MK-801 displacement. Unexpectedly, the 3- fluoro- primary amine 6 had the greatest affinity of the series and these binding results support a different structure activity relationship (SAR) profile for arylcycloheptylamines when compared to arylcyclohexylamines like PCP. Five of the novel compounds have affinity (Ki) in the hundred nM (10-7) range. In addition, compounds 3, 5, 6, 7 and 8 were evaluated and found to exhibit neuroprotective effects from NMDA induced toxicity in vitro and compounds 6, 7 and 8 exhibited anticonvulsant activities in rats. An ED50 of 13.84 mg/kg was found for compound 6 in rat maximal electroshock (MES) test with a protective index (PI) of 3.66 against ataxia. These results support further investigation of the arylcycloheptylamine class.
Keywords: arylcyclohexylamines